An Effort to Improve Compressibility of Mannitol - WISMIATI (NIM 10704032), MIA
Mannitol is widely used in pharmaceutical formulations as tablet diluent, eventhough it is poor in flowing and compressibility. Therefore, direct compression method can not be used for tablet preparation which use mannitol as diluent. Mannitol often used together with sorbitol as diluent in tablet formulation in order to improve its hardness. The aim of this study was to improve its flow property and compressibility. Physical mixtures (CF) and recrystallized mixtures of sorbitol and mannitol were prepared at the ratio of 1:9; 1:7; 1:5; 1:3; 3:7; 1:1; 7:3 dan 9:1 (w/w). Recrystallized mixtures were prepared using water to dissolve the mixtures. Physical and intermolecular interaction between sorbitol and mannitol were characterized by characterizing crystal habit under polarization microscope and thermal analysis using capillary and DSC (Differential Scanning Calorimetry) method. Flow rate, bulk density, tapped density and percent of compressibility of the mixtures (25-400 um) were evaluated. Several ratio of the physical and recrystallized mixtures were tableted using direct compression method. Furthermore the hardness and disintegration time of tablet were evaluated. Crystal habit of recrystallized mixtures showed spherical form while ratio of sorbitol in the mixtures increasing. Phase diagram of the binary mixtures of sorbitol-mannitol showed an eutectic system. The tablets formulated from recrystallized mixtures of sorbitol-mannitol (1:1) was the strongest with hardness 10.18 kg/cm2. The disintegration time of this tablet was 3 minutes and 4 seconds.